Tiron Mitigates Thioacetamide-Induced Acute Liver Injury - Shoeib, Amal Mahmoud; Said, Eman; Nader, Manar Ahmed; Salem, Hatem Abd-Elrahman; Ammar, Elsayed Mohamed (Fakultas Farmasi, Universitas Gadjah Mada, 2015)
Acute liver injury is a crippling disorder accompanied by extensive impairment of liver’s synthetic, metabolic and detoxifying functions. Tiron is a synthetic vitamin E analog, proven to be anti-oxidant. This study was undertaken to investigate the protective activity of tiron against thioacetamide (TAA)-induced acute liver injury. Rats were orally treated with tiron (300 mg/kg) for eight days prior to I.V. TAA either (70 mg/kg) or (280 mg/kg) to induce acute liver injury. Biochemical evaluation of hepatotoxicity indices, oxidative stress, cytotoxicity and inflammatory marker: interleukin-6 (IL-6) was conducted along with histopathological examination. Meanwhile, tiron was found to mitigate the TAA-induced elevation of ALT, AST and ALP. However, serum albumin levels mildly improved. Tiron restored liver GSH contents and maintained liver SOD activity. Moreover, tiron significantly reduced the level of serum IL-6. In context, histopathological examination revealed that tiron slightly reduced the extent of TAA-induced necrosis. Tiron has manifested the observed hepatoprotective effect probably by manipulating inflammatory response of liver to injury via downregulating the expression of inflammatory IL-6 and alleviating oxidative stress.